Faktor Risiko Kegagalan Antibiotika Empirik pada Pneumonia Anak (Studi Retrospektif) - Retno Asih Setyoningrum; Dewi Rahmawati (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2020)
Introduction: The aetiologies of childhood pneumonia were varies. Initial therapy of pneumonia based on clinical assessment, empirical antibiotic is unavoidable. Observation of the responses to empirical antibiotic therapy are needed, because not all children showed good response to those therapy. Objective to analyse the risk factors associated with empirical antibiotic treatment failure of childhood pneumonia.Methods: The study was conducted as observational analytic study with a retrospective research approach from 1 January 2014 - 31 December 2016 in the inpatient ward of Dr. Soetomo Hospital. Subjects were children aged 2-59 months with initial therapy of ampicillin and gentamicin, then assessed at 2-3 days of treatment.Results: There were 297 children with pneumonia aged 2-59 months, 42 (14%) subjects had empirical antibiotic treatment failure. The nine of variables studied, multivariate logistic regression analysis obtained pleural effusion (PR 7.25; p less than 0.001), atelectasis (PR 4.56; p 0.008), and thrombocytosis (PR 3.32; p 0.008) statistically significantly affected responses failure to empirical antibiotic.Conclusion: Pleural effusion, atelectasis and thrombocytosis are associated with the empirical antibiotic treatment failure in childhood pneumonia in Dr. Soetomo Hospital.